The Role of Microfinance in Driving MSME Growth: Challenges and Opportunities Amidst Economic Uncertainty - Mardiyah, Suci; Sudirman, Wahyu Febri Ramadhan (Journal of Financial and Business, 2025)
This study aims to analyze the role and effectiveness of microfinance in improving the resilience and performance of Micro, Small, and Medium Enterprises (MSMEs) amidst uncertain economic dynamics. MSMEs contribute significantly to Gross Domestic Product (GDP) and employment, but still face various obstacles, particularly in access to formal financing, limited capital, and low financial literacy. This study uses a library research method with a qualitative approach. Data were obtained through searching and analyzing various literature sources such as scientific journals, books, research reports, and official documents relevant to the topic of microfinance and MSME development. Data were analyzed descriptively and analytically to identify patterns of findings, research gaps, and conceptual synthesis related to the effectiveness of microfinance. The results of the study indicate that microfinance plays a significant role in improving capital access, productivity, and the sustainability of MSME businesses. In addition, support for the digitalization of financial services and innovation in financing models contribute to expanding financial inclusion. However, financing effectiveness is strongly influenced by factors such as financial literacy, managerial capacity, and adequate policy support. This study concludes that microfinance serves not only as a credit instrument but also as an economic empowerment strategy capable of sustainably strengthening the resilience of MSMEs.